A metallic 3D printed miniaturized circularly polarized log periodic Koch‐dipole array antenna. Issue 7 (9th April 2021) - Xiong, Yichen; Zhang, Bing
Abstract: A miniaturized circularly polarized (CP) log periodic Koch‐dipole array antenna (LPKDA) is proposed. Two pairs of dipoles are orthogonally deployed along the feeding line to generate the CP EM wave. The antenna's size is miniaturized by the T‐shaped top loading and the Koch fractal structure, which also helps to widened the antenna's axial ratio bandwidth. Compared with the conventional LPDA of the same impedance bandwidth, the proposed miniaturized CPLPKDA features 42%‐dimensional reduction. Taking the advantage of 3D printing technology to fabricate complex structures, the proposed CPLPKDA is fabricated by selective laser melting (SLM) using aluminum alloy. Measurement shows that the antenna has the average gain of 5.1 dBi from 2.1 to 3.0 GHz. It has impendence bandwidth (IBW) from 1.65 to 3.73 GHz (77.3%) and axial ratio bandwidth (ARBW) from 2.1 to 2.95 GHz (33.6%). Desirable radiation patterns are achieved. This letter proves the feasibility of antenna optimization by using both innovative design and advanced fabrication process.